Development of a hierarchical double application of crisp cluster validity indices: a proof-of-concept study for automated FTIR spectral histology. Issue 7 (28th January 2015) - Nguyen, Thi Nguyet Que; Jeannesson, Pierre; Groh, Audrey; Guenot, Dominique; Gobinet, Cyril
Abstract : The hierarchical double application of crisp cluster validity indices for automated spectral histology of a normal human colon. Abstract : Fourier-transform infrared (FTIR) spectral imaging is currently used as a non-destructive and label-free method for analyzing biological specimens. However, to highlight the different tissue regions, unsupervised clustering methods are commonly used leading to a subjective choice of the number of clusters. Here, we develop a hierarchical double application of 9 selected crisp cluster validity indices (CCVIs) using K-Means clustering. This approach when tested first on an artificial dataset showed that the indices Pakhira–Bandyopadhyay–Maulik (PBM) and Sym-Index (SI) perfectly estimated the expected 9 sub-clusters. Then, the concept was applied to a real dataset consisting of FTIR spectral images of normal human colon tissue samples originating from 5 patients. PBM and SI were revealed to be the most efficient indices that correctly identified the different colon histological components including crypts, lamina propria, muscularis mucosae, submucosa, and lymphoid aggregates. In conclusion, these results strongly suggest that the hierarchical double CCVI application is a promising method for automated and informative spectral histology.